Sosialisasi Penyusunan Perangkat Pembelajaran Berdeferensiasi Matematika Kelas 1 Materi Bentuk Bangun Datar - Arsya GP, Alfiana; Friska Anggraini S; Rosyid Khoirul N; Putri Zudhah Ferryka (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
This community service activity aims to socialize the importance of preparing differentiated teaching modules among educators. The preparation of differentiated teaching modules is one strategy in creating an inclusive learning experience that can be adjusted to the needs, interests, and abilities of diverse students. This activity involves fourth semester students from the PGSD study program, with a focus on developing their abilities in designing effective and responsive teaching modules to individual differences in students. Socialization is carried out through material presentations, discussions on the preparation of teaching modules, which are expected to improve educators' skills in implementing a differentiated learning approach. The results of this activity show an increase in participants' understanding of the concept of differentiated teaching modules and their ability to adapt learning materials according to student needs. This activity makes a significant contribution to efforts to improve the quality of education by presenting learning that is more relevant, inclusive, and oriented towards the diversity of students.